Targeting 3′ and 5′ untranslated regions with antisense oligonucleotides to stabilize frataxin mRNA and increase protein expression. Issue 20 (28th October 2021) - Li, Yanjie; Li, Jixue; Wang, Jun; Lynch, David R; Shen, Xiulong; R. Corey, David; Parekh, Darshan; Bhat, Balkrishen; Woo, Caroline; Cherry, Jonathan J; Napierala, Jill S; Napierala, Marek
Abstract: Friedreich's ataxia (FRDA) is a severe multisystem disease caused by transcriptional repression induced by expanded GAA repeats located in intron 1 of the Frataxin ( FXN ) gene encoding frataxin. FRDA results from decreased levels of frataxin; thus, stabilization of the FXN mRNA already present in patient cells represents an attractive and unexplored therapeutic avenue. In this work, we pursued a novel approach based on oligonucleotide-mediated targeting of FXN mRNA ends to extend its half-life and availability as a template for translation. We demonstrated that oligonucleotides designed to bind to FXN 5′ or 3′ noncoding regions can increase FXN mRNA and protein levels. Simultaneous delivery of oligonucleotides targeting both ends increases efficacy of the treatment. The approach was confirmed in several FRDA fibroblast and induced pluripotent stem cell-derived neuronal progenitor lines. RNA sequencing and single-cell expression analyses confirmed oligonucleotide-mediated FXN mRNA upregulation. Mechanistically, a significant elongation of the FXN mRNA half-life without any changes in chromatin status at the FXN gene was observed upon treatment with end-targeting oligonucleotides, indicating that transcript stabilization is responsible for frataxin upregulation. These results identify a novel approach toward upregulation of steady-state mRNA levels via oligonucleotide-mediated end targeting that may be of significance to any condition resulting from transcription downregulation.